Hypertension in High Risk African Americans 2014
DOI: 10.1007/978-1-4939-2010-5_3
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Lifestyle Changes to Decrease Unhealthy Eating Patterns and Improve Blood Pressure in African Americans

Abstract: Prevention and effective control of high blood pressure is critical, and hypertension management is often diffi cult even with intensive pharmacological therapy. Although the majority of adults with hypertension, over 74 million in the United States, including over two million new cases per year, are given prescription medications to control high levels of blood pressure, many have not reduced their blood pressure to less than 140/90 mmHg [ 17 ]. Shimbo et al. [ 29 ] suggest that once hypertension is resistant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…38,39 In contrast, other studies conducted in similar samples found that attitude and social norms do influence self-management. 24,25 While it is possible that information behaviors were more important factors in this sample, it is important to note that there was little variance in attitudes and social norms in this sample. Future studies should further evaluate the importance of these concepts among African American women attempting to manage their hypertension.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…38,39 In contrast, other studies conducted in similar samples found that attitude and social norms do influence self-management. 24,25 While it is possible that information behaviors were more important factors in this sample, it is important to note that there was little variance in attitudes and social norms in this sample. Future studies should further evaluate the importance of these concepts among African American women attempting to manage their hypertension.…”
Section: Discussionmentioning
confidence: 88%
“…5,11,21,22 Patients' attitude towards a behavior, such as management of hypertension, is an important cognitive domain to consider when determining their capacity for self-management. 23-25 Subjective norms, or social pressure that one perceives, is also related to participation in self-management activities. 26 In addition, self-management of hypertension requires that patients learn new information and skills.…”
Section: Introductionmentioning
confidence: 99%
“…One of the main purposes of self-management is to enable patients with hypertension to be closely engaged in self-care which is an essential requirement for long-term blood pressure control [ 34 ]. However, the rate of self-management is still considerably low among African American older adults with hypertension [ 35 ] as African Americans have been documented to have low adherence levels to lifestyle recommendations [ 36 , 37 ] and to engage in unhealthy behaviors such as physical inactivity, consumption of high fat and sodium containing foods, and tobacco and alcohol use [ 38 , 39 ]. This supports studies by psychological scientists who have indicated that individuals increasingly struggle with negative behaviors and find it hard to adopt and maintain healthier behaviors [ 40 ].…”
Section: Introductionmentioning
confidence: 99%